Sonographic Assessment of Intravascular Fluid Estimate (SAFE) Score by Using Bedside Ultrasound in the Intensive Care Unit - Keith Killu; Victor Coba; Dionne Blyden; Semeret Munie; Darlene Dereczyk; Pridvi Kandagatla; Amy Tang (Critical Care Research and Practice)
Objective. The objective of the study was to use an ultrasound-based numerical scoring system for assessment of intravascular fluid estimate (SAFE) and test its validity. Methods. A prospective, observational study was carried out in the surgical intensive care unit (ICU) of an urban tertiary care teaching hospital. Patient’s intravascular volume status was assessed using the standard methods of heart rate, blood pressure, central venous pressure, cardiac output, lactate and saturation of venous oxygen, and others. This was compared with assessment using bedside ultrasound evaluation of the cardiac function, inferior vena cava, lungs, and the internal jugular vein. Applying a numerical scoring system was evaluated by Fisher’s exact testing and multinomial logistic model to predict the volume status based on ultrasound scores and the classification accuracy. Results. 61 patients in the ICU were evaluated. 21 (34.4% of total) patients diagnosed with hypovolemia, and their ultrasound volume score was −4 in 14 (66.7%) patients, −3 in 5 (23.8%) patients, and 0 in 2 (9.5%) patients (p<0.001). 18 (29.5% of total) patients diagnosed with euvolemia, and their ultrasound volume score was 0 in 11 (61.1%) patients, +1 in 4 (22.2%) patients, and −1 in 1 (5.6%) patient (p<0.001). 22 (36.1% of total) patients diagnosed with hypervolemia, and their ultrasound volume score was +4 in 4 (18.2%) patients, +3 in 15 (68.2%) patients, and  + 1 in 1 (4.6%) patient (p<0.001). We found a strong association between standard measures and the ultrasound score (p<0.001). Conclusion. Using the SAFE scoring system to identify the IVV status in critically ill patients significantly correlates with the standard measures. A SAFE score of −4 to −2 more likely represents hypovolemia, −1 to +1 more likely represents euvolemia, and +2 to +4 more likely to be hypervolemia.